Identifying genetic biomarkers for diagnosis of prostate cancer in South African men - Salukazana, Samkele Azola (Division of General Surgery, 2021)
Background and Aim: Prostate cancer (PCa) is the leading cancer diagnosis amongst South African men. The incidence of PCa is 68.0 per 100 000 Age Standardized Rate (ASR) and the mortality rates are 27.9 per 100 000 ASR; Globocan 2018. Diagnosis of PCa is based on a combination of digital rectal examination, prostate-specific antigen (PSA) and histology. Several biomarkers have been used to increase the sensitivity and specificity of PSA in distinguishing patients with PCa from those with benign prostatic hyperplasia (BPH). These include fractionated PSA, free/total PSA ratio, −2proPSA, prostate cancer antigen 3 and prostate health index amongst others. Biomarkers are needed to differentiate BPH from PCa due to a lack of specificity of these markers with PSA levels above 4.0 ng/ml. The aim of this study is to investigate gene expression patterns of South African men in 9 PCa and 10 BPH patients in order to distinguish between the two groups. Methods: Ethical approval was obtained (HREC 454/2012). Patients scheduled for transurethral resection of the prostate were recruited from the Western Cape. RNA was extracted from prostate tissue using the AllPrep DNA/RNA/miRNA Universal Kit (Qiagen). Complementary DNA was synthesized from RNA using the SuperScript IV VILO Master Mix (Thermo Fischer Scientific). Gene expression was analyzed with the Human Prostate Cancer RT2 Profiler PCR Array and SYBR Green Master Mix. Data were analyzed with the GeneGlobe RT2 and miScript PCR Array Data Analysis Centre from Qiagen. Results: The cohort included patients from different ethnic groups namely, Caucasians, Mixedand African ancestry. The PCa group has an age range from 56 to 75 years (mean 65) while the BPH group was slight older ranging from 60 to 76 years (mean 68). PSA levels range from 24 to 5000 ng/ml (mean 1252 ng/ml, median 185) for the PCa group and 11 to 58 ng/mL (mean 25 ng/ml, median 22) for the BPH group. The following genes were downregulated 2-fold in the PCa group with p values s <0.05; IGF1, PTEN, GSTP1, SOCS3, EGR3, GPX3, TIMP3, ZNF185, DKK3, PTGS2, FOXO1, ARNTL, TNFRSF10D, CCND1, and DLC1, upregulated genes included; CDH1, MKI67, TMPRSS2, ERG, CDKN2A, FASN, and AR but were not statistically significant. At a fold change threshold of 1.5, the following additional genes were downregulated in the PCa group with p values <0.05; DAXX, EGFR, RASSF1, SOX4, and TIMP2, upregulated genes were ACACA, AR, CDKN2A, ERG and FASN but were also not statistically significant. The study shows similarly differentially expressed genes as seen in international studies. Of note PTEN, MKI67 and FASN which are associated with poor prognosis. EGR3 was downregulated in our study and this has been associated aggressive disease and predict relapse after PCa treatment. This could explain the high mortality demonstrated in South African epidemiological studies. Conclusion: We identified a group of differentially expressed genes that have potential in distinguishing PCa and BPH patients with PSA values above 10 ng/ml. A larger population study is needed to further evaluate the clinical significance of our findings.